THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON THE CUSTOMER LOYALITY AT THE RSIA BUNDA ANISYAH IN AIRTIRIS - Indah Purnama Sari; Librina Tria Putri; Yulizar Baharuddin (Jurnal Riset Manajemen Indonesia, 2020)
Research to determine the effect of Customer Reationship Management (CRM) which consist of competence, service, knowledge, procedures and technology with simulthan and partial on the customer loyality at the RSIA Bunda Anisyah in Airtiris. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all consumers who carry out pregnancy control at the RSIA Bunda Anisyah in Airtiris in 2019, amounting to 583 consumers and based on the Slovin formula it is know that the number of samples in this study is 85 consumers who carry out pregnancy control at the RSIA Bunda Anisyah in Airtiris. The sample collection technique is using accidental sampling technique. Data analysis was performed using multiple linear regression models. Based on the simulthan and partial test results, the variable of competence, service, knowledge, procedures and technology have a significant effect on the customer loyality at the RSIA Bunda Anisyah in Airtiris. The closeness of the relationship that occurs between the atractiveness competence, service, knowledge, procedures and technology on the customer loyality at the RSIA Bunda Anisyah in Airtiris is very strong with a correlation coefficient R of 86,0%. While contribution of independent variables to the dependent variables is equual to 72,9% while the remaining 27,1% is influenced by other variables not examined in this study.